Developing scale for colleague solidarity among nurses in Turkey - ALPAR, ŞULE (WILEY, 2013)
There is a need for an appropriate instrument to measure colleague solidarity among nurses. This study was carried out to develop a Colleague Solidarity of Nurses' Scale (CSNS). This study was planned to be descriptive and methodological. The CSNS examined content validity, construct validity, testretest reliability and internal consistency reliability. The trial form of the CSNS, which was composed of 44 items, was given to 200 nurses, followed by validity and reliability analyses. Following the analyses, 21 items were excluded from the scale, leaving an attitude scale made up of 23 items. Factor analysis of the data showed that the scale has a three sub-factor structure: emotional solidarity, academic solidarity and negative opinions about solidarity. The Cronbach's alpha reliability of the whole scale was 0.80. This study provides evidence that the CSNS possesses robust solidarity among nurses.
Keywords: colleague; instrument development; nurse; solidarity; validity and reliability; SUPPORT